PANDANGAN MUSLIMAH JOGJA TERHADAP RELASI GENDER (STUDI JEMAAH PENGAJIAN YAYASAN RUMPUN NURANI YOGYAKARTA) - Elpipit, Elpipit; Hardiyatullah, Hardiyatullah; Hamroni, Hamroni (STIS Darussalam Bermi, 2023)
Abstrak The discussion on the subject of gender in family law has been discussed more and more in light of both acamedic and gender activist? male views, and it is rarely asked for a famale?s opinion. Based on these studies the research in this article probes the famale?s view. Given how: the current reality in the field that demonstrates women?s lives in urban areas with her few public duties, wether their involvement in the public domain coincided with her understanding of gender. Based on the pheemona in this thesis has at least two questions, namely how the view of urban Muslims about the gender relations of husband and wife and what is behind the emergence of the view of urban Muslimah. The results of the study are: First, the background of the emergence of the thoughts and views of Jemaahn Yayasan Rumpun Nurani Foundation on the gender relations of husband and wife is at least influenced by three factors, namely religious understanding, science and knowledge, and social and cultural factors formed from personal experience. Second, Jamaah Pengajian Yayasan Rumpun Nurani considers that husband and wife relationships in the family do not have a fundamental difference between husband and wife. In terms of domestic labor division and decision-making is done flexibly, but for the fulfillment of family needs, it is entirely the husband's responsibility. Based on this view, urban Muslims can be said to be gender conscious Muslims